Climate Policy and Economic Growth in Developing Countries - Barbara Buchner; Marzio Galeotti (Fondazione Eni Enrico Mattei (FEEM), 2003)
Although developing countries face a drastic increase in their greenhouse gas emissions, mitigation actions against climate change do not rank high among their priorities. The obvious reason lies in the necessity for them to continue the development process, which is characterised by pressing needs other than emission control. For developing countries the real problem is thus not emissions but economic growth. Therefore the key question is whether or not the Kyoto Protocol provides an opportunity for growth and thus for their economic development. The only way to accelerate the participation of developing countries in climate agreements - and therefore to come closer to the goal of a global climate control - is to design strategies which enable their economic development. The dilemma of reducing emissions on a global scale while ensuring growth in the poorer regions can only be solved if there are possibilities embedded in the agreements which can contribute to the sustainable development of those regions. As a consequence, greater emphasis must be placed on the economic development dimension of the Kyoto Protocol as far as the impact on developing countries is concerned.
Keywords: H0; H2; H3; 330; Climate Policy; Environmental Modeling; Integrated Assessment; Technical Change; Klimaschutz; Wirtschaftswachstum; Umweltbewertung; Technischer Fortschritt; Entwicklungsländer